The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.clim.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automated and standardized cytometric procedures for multi-panel and multi-parametric whole blood immunophenotyping

Abstract: Immunophenotyping by multi-parametric flow cytometry is the cornerstone technology for enumeration and characterization of immune cell populations in health and disease. Standardized procedures are essential to allow for inter-individual comparisons in the context of population based or clinical studies. Herein we report the approach taken by the Milieu Intérieur Consortium, highlighting the standardized and automated procedures used for immunophenotyping of human whole blood samples. We optimized eight-color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 25 publications
3
41
0
6
Order By: Relevance
“…To our knowledge, these findings are the first to describe the performance of immunophenotyping in cryopreserved blood, and are very similar to that reported in fresh blood (29). We found that while the correlation of estimates obtained on different days was consistently high (>0.78), coefficient of variation (CV) estimates (inter-or intra-assay) were slightly higher for pDCs, basophils and NKT cells.…”
Section: Cytometry Part B: Clinical Cytometrysupporting
confidence: 83%
“…To our knowledge, these findings are the first to describe the performance of immunophenotyping in cryopreserved blood, and are very similar to that reported in fresh blood (29). We found that while the correlation of estimates obtained on different days was consistently high (>0.78), coefficient of variation (CV) estimates (inter-or intra-assay) were slightly higher for pDCs, basophils and NKT cells.…”
Section: Cytometry Part B: Clinical Cytometrysupporting
confidence: 83%
“…Over the past three decades, flow cytometry has been widely applied for immune‐phenotyping in clinical and research settings 1, 2, 29, 30, 47, 65, 66, 67, 68, 69, 70. A 17‐multiparamentric assay has been developed in the past for analyzing in details PB mature cells 68.…”
Section: Discussionmentioning
confidence: 99%
“…A reference dataset is constructed and new samples, analysed with the same panels, can be mapped onto this reference to classify a patient. Also in larger community-wide efforts, such as the Human Immunology Project Consortium (HIPC) 25 or the Milieu Interieur project 26 , the design of standardized panels is of key importance. To facilitate sharing and dissemination of optimized panels, the cytometry community has recently introduced a new series of protocols to improve reproducibility, referred to as optimized multicolour immunofluorescence panels (OMIPs) 27 .…”
Section: Standardization and Reproducibilitymentioning
confidence: 99%